DESIGNING SECURE COMPUTER ARCHITECTURES FOR DATA PROTECTION IN NEXT-GENERATION NETWORKS - PRAVORSKA, NATALYA; DOMINA, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article is devoted to the important issue of designing secure computer architectures for data protection in next-generation networks. It analyzes current trends in computer architecture and data security, as well as challenges and problems faced by modern computer networks. In the field of computer architecture, one of the key trends is the transition from centralized to distributed systems, which leads to new problems and challenges, such as: protection against unauthorized access to data; protection against denial of service (DoS attacks); vulnerability to physical attacks, etc. The purpose of this study is to develop a new approach to designing computer architectures that takes into account the needs for data security in the context of modern next-generation computer networks. To achieve this goal, the main tasks were identified: conducting an analysis of modern computer and network architectures; developing a strategy for integrating data protection tools at the architecture level; evaluating the effectiveness of the proposed approach.  After analyzing modern architectures, the application of secure computer architectures in next-generation networks is presented, namely, scenarios for the application of secure computer architectures in next-generation networks. The article considers various scenarios for the above architectures, including IaaS, private networks, edge computing, IoT, blockchain, and HPC. The author proposes a new approach to designing secure computer architectures, which is based on the integration of data protection tools directly at the architecture level. Based on the presented materials, practical results are presented with a consistent analysis of the above application, namely: increasing the level of data security; availability of adaptability to changing conditions and challenges; efficiency in resource use; increasing user trust.
Keywords: data security; computer architecture; next-generation networks; IaaS; private networks; edge computing; IoT; blockchain; HPC; systems design; software engineering